Effect of high-dose sulfamethoxazole/trimethoprim and glucocorticoid use on hyperkalemic event: A retrospective observational study. Issue 11 (November 2021) - Hirai, Toshinori; Yamaga, Ryosuke; Ishikawa, Yutori; Hanada, Kazuhiko; Iwamoto, Takuya; Itoh, Toshimasa
Abstract: Introduction: Sulfamethoxazole/trimethoprim causes hyperkalemia; however, the effect of sulfamethoxazole/trimethoprim dose and co-administered glucocorticoids on hyperkalemia has not been clarified. Methods: This single-center, retrospective, observational cohort, chart review study involving patients (>20 years) who were treated with sulfamethoxazole/trimethoprim was conducted at Tokyo Women's Medical University, Medical Center East from June 2015 to May 2019. Multivariate Cox proportional hazard model was used to identify risk factors for hyperkalemia (serum potassium level > 5.5 mEq/L). Additionally, Kaplan–Meier curve analyzed the cumulative incidence of hyperkalemia focusing on sulfamethoxazole/trimethoprim dose and concomitant use of glucocorticoids with mineralocorticoid activity. Results: Among 333 patients, 44 (13%) patients developed hyperkalemia associated with sulfamethoxazole/trimethoprim use for over 49 (interquartile range; 17–233) days. We found associations between the time to hyperkalemia development and sulfamethoxazole/trimethoprim dose (hazard ratio 1.238, 95% confidence interval 1.147–1.338, p < 0.001) and glucocorticoid use (hazard ratio 0.678, 95% confidence interval 0.524–0.877, p = 0.003). Interestingly, the Kaplan–Meier curves revealed that the concomitant use of glucocorticoids did not attenuate the risk of hyperkalemia in patients receiving high-dose sulfamethoxazole/trimethoprim (p = 0.747), whereas concomitant use of glucocorticoids significantly reduced the risk of hyperkalemia in patients receiving non-high dose sulfamethoxazole/trimethoprim (p < 0.001). Conclusions: High-dose sulfamethoxazole/trimethoprim is a significant predictor of hyperkalemia. The effect of glucocorticoids on hyperkalemia varies depending on the sulfamethoxazole/trimethoprim dose.